De Hyōgo à Sendai, la résilience comme impératif d’adaptation aux risques de catastrophe : nouvelle valeur universelle ou gouvernement par la catastrophe ? - Béatrice Quenault (Développement Durable et Territoires)
Since the adoption of the Hyōgo Framework for Action 2005-2015, resilience irrigates most of the United Nations discourses about disaster risk reduction (DRR) and is presented as an essential dimension of sustainable development pathways. The growing discursive reference to resilience, placed at the core of the Sendai Framework for Action 2015-2030 for DRR, tends to promote this concept as a new normative political injunction of international organisations and States leading to a renewal of the adaptation problematic and to focus DRR actions on emergency preparedness. Indeed, resilience could be exploited at the benefice of a neoliberal project of society susceptible to lead to a stigmatisation of most vulnerable communities and people in the opposite direction of collective solidarity aims implied by sustainable development.